Identification of ANKDD1B variants in an ankylosing spondylitis pedigree and a sporadic patient - Zhiping Tan; Hui Zeng; Zhaofa Xu; Qi Tian; Xiaoyang Gao; Chuanman Zhou; Yu Zheng; Jian Wang; Guanghui Ling; Bing Wang; Yifeng Yang; Long Ma (BMC, 2018)
Abstract Background Ankylosing spondylitis (AS) is a debilitating autoimmune disease affecting tens of millions of people in the world. The genetics of AS is unclear. Analysis of rare AS pedigrees might facilitate our understanding of AS pathogenesis. Methods We used genome-wide linkage analysis and whole-exome sequencing in combination with variant co-segregation verification and haplotype analysis to study an AS pedigree and a sporadic AS patient. Results We identified a missense variant in the ankyrin repeat and death domain containing 1B gene ANKDD1B from a Han Chinese pedigree with dominantly inherited AS. This variant (p.L87V) co-segregates with all male patients of the pedigree. In females, the penetrance of the symptoms is incomplete with one identified patient out of 5 carriers, consistent with the reduced frequency of AS in females of the general population. We further identified a distinct missense variant affecting a conserved amino acid (p.R102L) of ANKDD1B in a male from 30 sporadic early onset AS patients. Both variants are absent in 500 normal controls. We determined the haplotypes of four major known AS risk loci, including HLA-B*27, 2p15, ERAP1 and IL23R, and found that only HLA-B*27 is strongly associated with patients in our cohort. Conclusions Together these results suggest that ANKDD1B variants might be associated with AS and genetic analyses of more AS patients are warranted to verify this association.